1998
DOI: 10.1046/j.1365-2362.1998.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of gp330/megalin expression by vitamins A and D

Abstract: The results indicate a correlation between exposure to retinoic acid or vitamin D or induction of cell differentiation (by retinoic acid/cAMP in F9 cells or inhibition of SV40 transcription in IRPTCs) and an increase in gp330/megalin protein and mRNA expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
2
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 30 publications
3
56
2
2
Order By: Relevance
“…Since the apelin receptor APJ is not detectable in this renal structure, the effect of APLN-13 may be indirect. Megalin mRNA expression in the proximal tubules is stimulated by various factors, including vitamin A and vitamin D (33). The mechanism by which Apelin regulates megalin expression remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Since the apelin receptor APJ is not detectable in this renal structure, the effect of APLN-13 may be indirect. Megalin mRNA expression in the proximal tubules is stimulated by various factors, including vitamin A and vitamin D (33). The mechanism by which Apelin regulates megalin expression remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Because it is known that megalin expression is positively regulated by vitamin D through VDR (55) and recently it was demonstrated that LCA is a ligand for VDR (41), we decided to explore the possibility that megalin expression was regulated, in vitro and in vivo, by BAs as LCA. In vitro, megalin expression was greatly decreased at LCA concentrations that activate its known mediator FXR (Ͼ25 M) and was slightly increased or not changed by lower concentrations of LCA that activate VDR (5-10 M) (41).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that megalin expression is regulated by retinoic acid and vitamin D suggests the involvement of the transcription factors vitamin D receptor (VDR) and retinoid X receptor (RXR) in its regulation (55). Because the hydrophobic secondary BA LCA binds with high affinity to VDR (41), it is also possible that the expression of megalin could be regulated by BAs.…”
Section: Regulation Of Megalin Protein Expression By Bas In Vitromentioning
confidence: 99%
“…At the transcriptional level, megalin mRNA expression is augmented by retinoic acid (vitamin A) and vitamin D treatment in cells from different origins and species (Liu et al, 1998). Both vitamins A and D carried by their specifi c vitamin binding proteins, RBP and DBP, are endocytosed by megalin.…”
Section: Regulation Of Megalin Mrna and Protein Expressionmentioning
confidence: 99%
“…In breast cancer cells, the expression of megalin, its coreceptor cubilin and the adaptor protein Dab2 are induced by retinoic acid (Chlon et al, 2008). The differentiation state of cells, such as rat PT cells and F9 embryonal carcinoma cells, also positively regulates the expression of megalin (Liu et al, 1998). For example, the differentiation of F9 cells with retinoic acid and cAMP induces the expression of megalin protein and of the RAP (Czekay et al, 1995).…”
Section: Regulation Of Megalin Mrna and Protein Expressionmentioning
confidence: 99%